An event-related potential investigation of sentence processing in adults who stutter. (May 2016) - Murase, Shinobu; Kawashima, Takashi; Satake, Hirotaka; Era, Seiichi
Graphical abstract: Highlights: Semantic processing in adults who stutter was examined by event-related potentials. Adults who stutter attenuated the N400 and enhanced the late LPC. Semantic processing in adults who stutter differs and may be more time consuming. Abstract: The purpose of this study was to investigate characteristics of the semantic processing of sentences' final verbs in stutterers using event-related potential (ERP). ERPs elicited from semantically violating and non-violating verbs in Japanese sentences were compared between 13 adults who stutter (AWS) and 13 adults who do not stutter (AWNS). The stimulus sentences elicited the N400 and the late positive component (LPC) in both groups. The amplitude of the N400, however, was attenuated in AWS. Regarding the LPC, the LPC in the 450–700 ms time window (the early LPC) was evident in both groups, but the LPC in the 700–850 time window (the late LPC) was only apparent in AWS. Because AWS judged sentence congruency as accurately as AWNS did, it is assumed that AWS depended more on the LPC for semantic processing, resulting in the enhancement of the late LPC. We speculate that semantic processing of sentences for AWS is more time consuming than that for AWNS.